Gas Price Policy Analysis for Fertilizer Industries in Indonesia Based on Netback from Final Product - Erwan Hermawan; Widodo Wahyu Purwanto (Jurnal Sosial Humaniora, 2020)
The industrial sector has an important role in the Indonesian economy. Theproblem facing the fertilizer industry is the price of gas as a raw material thattends to be expensive for the lower prices of crude oil since 2016. To overcomethis problem the government issued Presidential Regulation No. 40/2016 onsetting gas prices for the fertilizer industry but this regulation only sets floorgas prices at USD 6/MMBTU to secure revenues of gas producers.Meanwhile, the current sale gas contract for fertilizer applies an escalation.The objectives of this study are to evaluate the netback value of each fertilizerplant and assess the current gas price policy. The netback value is calculatedbased on the long-run marginal cost of urea production. The result shows thatPKT 04 and PKT 05, Pusri 1B, 2B, 3, and 4, PKC 1A and 1B, and PKG havelower netback value than gas price contract, except for PKT plant based onaverage has the highest netback value, because they use pricing mechanismthat linked to oil and product price. From this calculation the current gasprice policy needs to be adjusted to keep the fertilizer industry profitably.